Comparison of Dexmedetomidine, Lidocaine, and Fentanyl in Attenuation Hemodynamic Response of Laryngoscopy and Intubation in Patients Undergoing Cardiac Surgery. (1st July 2020) - Mahjoubifard, Maziar; Heidari, Mehdi; Dahmardeh, Maryam; Mirtajani, Seyed Bashir; Jahangirifard, Alireza
Abstract : Introduction and Objective . Laryngoscopy and intubation are accompanied by sympathetic responses. These transient responses appear as an increase in blood pressure and heart rate. In patients with cardiovascular problems, the hemodynamic changes may lead to life-threatening risks, such as heart ischemia, acute heart failure, and cerebrovascular events. Materials and Methods . This clinical trial was conducted on 90 patients, aged 30–70 years, who had heart surgery. The participants were categorized into three groups. Group D received 1  µ g/kg intravenous dexmedetomidine in 10 minutes, group L received 1.5 mg/kg lidocaine (1%) 90 seconds before intubation, and group F received 2  µ g/kg fentanyl. The vital signs (HR, SBP, DBP, and MAP) were measured before intubation and 1st, 3rd, 5th, and 10th minutes after intubation. Data were analyzed with SPSS 19 software (chi-square, one-way ANOVA, or Kruskal–Wallis). Results . The age (P = 0.389 ) and gender distributions of patients were similar in all three groups. Dexmedetomidine significantly attenuated HR in the 3 rd (P = 0.001 ), 5 th (P = 0.001 ), and 10 th (P = 0.003 ) minutes after intervention. It also reduced the systolic blood pressure in the 5 th (P = 0.024 ) and 10 th (P = 0.006 ) minutes. This reduction was significantly higher in the dexmedetomidine group than that in the two other groups. In addition, dexmedetomidine caused a greater reduction in MAP in the 1 st (P = 0.048 ), 5 th (P = 0.0001 ), and 10 th (P = 0.0001 ) minutes. Discussion . All three medications were effective in controlling HR; however, dexmedetomidine caused bradycardia in the 3 rd, 5 th, and 10 th minutes. Lidocaine resulted in an increase in MAP in the 1 st minute after intubation; whereas, dexmedetomidine reduced MAP at the 5 th and 10 th minutes after intubation. Changes in blood pressure and mean arterial pressure in the fentanyl group was lower than the two other groups. Conclusion . As a result, dexmedetomidine was not suitable for hemodynamic control and led to hypotension and bradycardia; on the other hand, fentanyl was more effective than two other medications in patients undergoing cardiac surgery. This trial is registered with IRCT2017013132320N1 .